Keratoacanthoma centrifugum marginatum: unresponsive to oral retinoid and successfully treated with wide local excision. - Kapildev Das; Nilay Kanti Das; Vikram Singh Rathore; Sourav Kundu; Sourav Choudhury; Ramesh Chandra Gharami; Pijush Kanti Datta (PAGEPress Publications, 2010)
We describe a case of a 65-year-old male presenting with a large plaque with a rolled-out interrupted margin, atrophic center, and island of normal skin over the left arm. It grew peripherally with central healing, and there was a history of recurrence after inadequate excision. Investigations ruled out other clinical mimickers; namely, squamous cell carcinoma, lupus vulgaris, botryomycosis, and blastomycosis-like pyoderma. Histopathological sections showed irregularly shaped craters filled with keratin and epithelial pearl but no evidence of granuloma or cellular atypia. Clinicopathological correlation proved the lesion to be keratoacanthoma centrifugum marginatum (KCM), a rare variant of keratoacanthoma, which spreads centrifugally, attains a huge size, and never involutes spontaneously. Treatment of KCM has been a problem always and, in our case, systemic retinoid (acitretin for three months) proved ineffective. The patient also had a history of recurrence following surgical intervention previously, necessitating wide excision to achieve complete clearance of tumor cells. Hence, after failure of retinoid therapy, the decision of excision with a 1-centimeter margin was taken and the large defect was closed by a split thickness skin graft. The graft uptake was satisfactory, and the patient is being followed-up presently and shows no signs of recurrence after six months, highlighting wide local excision as a useful treatment option.